HUBUNGAN DISIPLIN BELAJAR DAN PRESTASI BELAJAR MAHASISWA DENGAN PERILAKUNYA DALAM MEMELIHARA KEBERSIHAN LINGKUNGAN KAMPUS - Gumilar, Rendra; Hermawan, Yoni (Bumi Lestari; Vol 16 No 1 (2016)DO - 10.24843/blje.2016.v16.i01.p07)
This study aims to find, analyze and examine the relationship between the discipline oflearning and achievement with behavior in maintaining the cleanliness of the environment.The study design used in this study was student class of 2011 Program StudiesEconomics Education / Administration Commerce Teacher Training and Education Facultyof the University of Siliwangi Tasikmalaya totaling 193 people. The sampling techniqueused in this study is proportional random sampling technique, the sample size of 60 people.Instrument in this study using a questionnaire to learn discipline and student behaviorquestionnaire in maintaining the cleanliness of the environment. While the data analysistechniques used were correlation analysis, simple and multiple regression.The results showed that the discipline variables studied included strong categories,including categories of academic achievement variable low and variable behavior of studentsin maintaining the cleanliness of the environment, including strong category.There is a relationship between the discipline of studying the behavior of students inmaintaining the cleanliness of the campus. This can be evidenced by the acquisition of an rvalue of 0.767 and a strong cohesion category contributes by 58.8%. The better the disciplineof learning, the better the behavior of students in maintaining the cleanliness of the campus.There is a relationship between the behavior of student achievement in maintaining thecleanliness of the campus. This can be evidenced by the acquisition of an r value of 0.319and a low of closeness category contributed 10.1%.The better achievement, the better thebehavior of students in maintaining the cleanliness of the campus.There is a relationshipbetween the discipline of learning and academic achievement with student behavior inmaintaining the cleanliness of the campus. This can be evidenced by the acquisition of an rvalue of 0.781 and a strong cohesion category contributes 61%. The better the discipline oflearning and the achievement of learning, the better the behavior of students in maintainingthe cleanliness of the campus.
Keywords: discipline studied, the achievement of learning, behavior, campus